Inspired 3D short film production - Cantor, Jeremy; Valencia, Pepe. (Boston : Thomson Course Technology/Premier Press, 2004)
A guide to creating short three-dimensional films that includes examples, exercises, case studies, and more to help producers understand the basic concepts, theories, and applications of 3D film production; includes a DVD with dozens of award-winning short films.
Includes bibliographical references (p. 443-446) and index.
Adult
Keywords: Computer animation; Three-dimensional display systems; Computer animation; Three-dimensional display systems